Preliminary outcomes of anterior ankle arthrodesis - Silveira, Juliana Doering Xavier da; Pereira, Vinicius Felipe; Masuda, Vitor Yoshiura; Azevedo, Rafael Mohriak; Mansur, Nacime Salomão Barbachan (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study was to evaluate preliminary clinical and radiographic outcomes of a case series of patients with ankle osteoarthritis undergoing anterior tibiotalar arthrodesis using anterior plate and cannulated screws as a form of fixation. Methods: We retrospectively assessed the clinical and radiographic outcomes of eight cases treated with this technique in our service between 2014 and 2017, using the American Orthopedic Foot and Ankle Score (AOFAS) questionnaire and radiographic evaluation in two orthogonal views with ankle weight bearing, evaluated at one year after surgery. Results: We obtained AOFAS scores between 38 and 92 in the late postoperative period and a consolidation rate of 87.5% (seven cases). There was consolidation failure in one case, which resulted in plate loosening and the need for reoperation. Only one of the patients presented superficial surgical wound complication, treated only with serial dressings. There were no neurovascular complications. Conclusion: The present study obtained adequate preliminary outcomes with the use of the demonstrated technique, indicating a possible advantage of the same in relation to conventional techniques and the possibility of using lower-cost surgical materials. Level of Evidence IV; Therapeutic Studies; Cases Series.